2020
DOI: 10.1515/tnsci-2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptome of the ventral tegmental area in a deep brain-stimulated chronic unpredictable mild stress mouse model

Abstract: Deep brain stimulation (DBS) applied to the nucleus accumbens (NAc) alleviates the depressive symptoms of major depressive disorders. We investigated the mechanism of this effect by assessing gene expression and RNA methylation changes in the ventral tegmental area (VTA) following NAc-DBS in a chronic unpredictable mild stress (CUMS) mouse model of depression. Gene expression and N6-methyladenosine (m6A) levels in the VTA were measured in mice subjected to CUMS and then DBS, and transcriptome-wide m6A changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…The behavior tests indicated that CUMS rats were presented with weakened sucrose preference, prolonged immobility time and escape latency, reduced traveling distance, shortened time to explore new objects and enter the open arms, and decreased time in the target quadrant and crossing‐platform number, indicating cognitive deficits in CUMS rats. Previous study has demonstrated that CUMS elevates m6A modification level in the DD mouse model and the abolishment of m6A modification promotes the antidepressant activity (Song, Du, Gao, & Yang, 2020; Wu et al, 2021). Accordingly, METTL3 along with m6A level was found to be increased in CUMS rats, in line with METTL3 upregulation in AD‐related cognitive deficits (Han et al, 2020; Mathoux et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The behavior tests indicated that CUMS rats were presented with weakened sucrose preference, prolonged immobility time and escape latency, reduced traveling distance, shortened time to explore new objects and enter the open arms, and decreased time in the target quadrant and crossing‐platform number, indicating cognitive deficits in CUMS rats. Previous study has demonstrated that CUMS elevates m6A modification level in the DD mouse model and the abolishment of m6A modification promotes the antidepressant activity (Song, Du, Gao, & Yang, 2020; Wu et al, 2021). Accordingly, METTL3 along with m6A level was found to be increased in CUMS rats, in line with METTL3 upregulation in AD‐related cognitive deficits (Han et al, 2020; Mathoux et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the deficiency of Mettl3 and Fto indicates the role of m6A/m regulatory genes in stress resilience [ 137 ]. m6A-mRNA methylation in the VTA increases in response to CUMS in comparison to unstressed animals [ 138 ]. Yan et al (2022) showed that treadmill exercise in RNA m6A homeostasis in the PFC plays a role by improving the resilience against CRS for one hour for 14 days [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“… 374 Another study showed that NAc-deep brain stimulation (DBS) could reverse the impacts of CUMS on gene expression and m 6 A-mRNA modification for certain genes, but the m 6 A-regulating enzymes were not detected. 375 …”
Section: Rna Modifications Participate In the Molecular Mechanisms Un...mentioning
confidence: 99%